Service design and fashion: relationships for the development of colaborative platforms (ModaPalavra e-periódico, 2021)
The impact generated by excessive consumption has brought, not only to the environment, but also to society and economy, consequences that question the longevity of the human species. In search of new practices for sustainable development, there are movements around the world, and more recently in Brazil, instigated by the contemporary context of innovation and technology, with consequences for change in processes and products. In fashion, which lacked a national identity for many decades, there is the emergence of collaborative service platforms that are disruptive to the sector. Thus, the objective is to understand the relationship of service design in the development of collaborative platforms for the Brazilian fashion sector. For this purpose, we proceed with exploratory research, with a qualitative approach and, as a method of data collection, bibliographical and documentary research. Thus, the potential of the Brazilian fashion market for innovation is observed, when approached by service design.
Keywords: innovation; sustainable development; creative economy